The Anthochron as a building block for flower development - Streck, Nereu Augusto; Schwab, Natalia Teixeira (Pesquisa Agropecuaria Brasileira, 2016)
Plant vegetative development has been widely described using the phyllochron concept, but little effort has been made to describe flower development during the reproductive phase. The objective of this work was to present the anthochron, through a review of the literature, as a building block of flower development, mainly during the flower opening phase. The anthochron is the time interval needed for two subsequent flowers to achieve the same developmental stage, with units of time in days or in ºC day per flower. The concept of anthochron fulfills part of the lack of studies on flower development, since it is considered a building block of the flower opening process. The anthochron can be measured from field experiments or estimated by a simple linear regression analysis. So far, the anthochron has only been quantified in Gladiolus x grandiflorus Hort. Therefore, factors affecting the anthochron still need to be determined in order to pinpoint their effect on the flower opening rate.